The Influence of Organizational Culture, Organizational Structure, and Information Technology Implementation on The Quality of Management Accounting Information Systems And Its Impact on Managerial Performance PT Kereta Api Indonesia (Persero) - Hafiizh, Aulia; Rachmawati, Rima (Dinasti Publisher, 2025)
The research aims to analyze the influence of organizational culture, organizational structure, and information technology implementation on the quality of Management Accounting Information Systems (MAIS) and the impact of MAIS quality on managerial performance. The research adopts a quantitative method with data analysis techniques using Partial Least Square (PLS) through SmartPLS software. The study sample consists of 78 respondents at PT KAI (Persero), comprising 38 respondents from the 1st line, 9 respondents from the 2nd line, and 31 respondents from the 3rd line. The results reveal that organizational culture has a significant influence on MAIS quality. In contrast, organizational structure does not significantly affect MAIS quality. Information technology implementation is proven to significantly influence MAIS quality. Furthermore, MAIS quality has a significant impact on managerial performance at PT KAI (Persero).